To solve the quadratic equation \( x^2 + 2x - 8 = 0 \) by completing the square, follow these steps:
-
Move the constant to the other side of the equation: \[ x^2 + 2x = 8 \]
-
Take the coefficient of \( x \) (which is 2), divide it by 2 (getting 1), and square it (getting 1). Add this value to both sides: \[ x^2 + 2x + 1 = 8 + 1 \] \[ x^2 + 2x + 1 = 9 \]
-
The left side factors as \( (x + 1)^2 \): \[ (x + 1)^2 = 9 \]
-
Take the square root of both sides: \[ x + 1 = 3 \quad \text{or} \quad x + 1 = -3 \]
-
Solve for \( x \): \[ x + 1 = 3 \quad \Rightarrow \quad x = 3 - 1 = 2 \] \[ x + 1 = -3 \quad \Rightarrow \quad x = -3 - 1 = -4 \]
Thus, the solutions are:
\[ x = 2, \quad x = -4 \]
The correct response is:
x=2, x=−4
x equals 2, x equals negative 4